2004
DOI: 10.1007/s00048-004-0201-3
|View full text |Cite
|
Sign up to set email alerts
|

The women radium dial painters as experimental subjects (1920–1990) or what counts as human experimentation

Abstract: The case of women radium dial painters - women who tipped their brushes while painting the dials of watches and instruments with radioactive paint - has been extensively discussed in the medical and historical literature. Their painful and abhorrent deaths have occupied the interest of physicians, lawyers, politicians, military agencies, and the public. Hardly any discussion has concerned, however, the use of those women as experimental subjects in a number of epidemiological studies that took place from 1920 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The reason for this significant difference in the incidence rate was that the head carcinoma seems to appear much later. The time of appearance for bone sarcoma was approximately 5 years, whereas 19 years for head carcinoma if the time of appearance was plotted against the initial systemic intake (Rowland, 1994). The highest systemic intake was the age at first exposure (AFE); values ranged from 16.0 to 21.7, which confirmed that the female radium dial workers were very young.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The reason for this significant difference in the incidence rate was that the head carcinoma seems to appear much later. The time of appearance for bone sarcoma was approximately 5 years, whereas 19 years for head carcinoma if the time of appearance was plotted against the initial systemic intake (Rowland, 1994). The highest systemic intake was the age at first exposure (AFE); values ranged from 16.0 to 21.7, which confirmed that the female radium dial workers were very young.…”
Section: Resultsmentioning
confidence: 85%
“…In 1967, data from separate studies were consolidated into a newly created Center for Human Radiology (CHR) at Argonne National Laboratory (ANL). Based on a followup of this consolidated data by the end of , Rowland, et al (1978) established a quasilog-linear model for the incidence rate of bone/head tumors as a function of the product between a quadratic function of exposure dose and an exponential function of exposure dose. They concluded that a model of dose-squaredexponential function provided the best fit for the bone sarcomas, and that an acceptable fit to the head carcinoma data was provided by the linear function of the dose.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations